Sucrose regulates wall ingrowth deposition in phloem parenchyma transfer cells in Arabidopsis via affecting phloem loading activity. (20th May 2020) - Wei, Xiaoyang; Nguyen, Suong T T; Collings, David A; McCurdy, David W
Abstract : Transfer cells involved in phloem loading are poorly understood. Exogenous and endogenous sucrose differentially affect wall ingrowth deposition in Arabidopsis phloem parenchyma transfer cells via modifying their phloem loading status. Abstract: In Arabidopsis thaliana, phloem parenchyma transfer cells (PPTCs) occur in leaf minor veins and play a pivotal role in phloem loading. Wall ingrowth formation in PPTCs is induced by the phloem loading activity of these cells, which is regulated by sucrose (Suc). The effects of endogenous versus exogenous Suc on wall ingrowth deposition, however, differ. Elevating endogenous Suc levels by increased light enhanced wall ingrowth formation, whereas lowering endogenous Suc levels by dark treatment or genetically in ch-1 resulted in lower levels of deposition. In contrast, exogenously applied Suc, or Suc derived from other organs, repressed wall ingrowth deposition. Analysis of pAtSUC2::GFP plants, used as a marker for phloem loading status, suggested that wall ingrowth formation is correlated with phloem loading activity. Gene expression analysis revealed that exogenous Suc down-regulated expression of AtSWEET11 and 12, whereas endogenous Suc up-regulated AtSWEET11 expression. Analysis of a TREHALOSE 6-PHOSPHATE (T6P) SYNTHASE overexpression line and the hexokinase (HXK)-null mutant, gin2-1, suggested that Suc signalling of wall ingrowth formation is independent of T6P and HXK. Collectively, these results are consistent with the conclusion that Suc regulates wall ingrowth formation via affecting Suc exporting activity in PPTCs.